Relationship of CDC group EO-2 and psychrobacter immobilis. - Hudson, M J (1987)
Thirty strains of microorganisms previously classified in the CDC group EO-2 were studied to determine the relationship of this group and the recently proposed Psychrobacter immobilis. Results of transformation studies indicated that 9 of the 30 studied strains should be reclassified as P. immobilis. While transformation studies should be used to identify the Psychrobacter genus definitively, some presumptive characteristics useful in differentiating the CDC group EO-2 and P. immobilis were observed. The Psychrobacter genus, compared with the CDC group EO-2, grew well at 25 degrees C, lightly or not at all at 35 degrees C, and not at all at 42 degrees C, grew in nutrient broth without NaCl and with only one exception grew in 6% NaCl, usually did not produce acid from adonitol, dextrin, fructose, or D-mannitol, did not demonstrate the O-shaped cellular morphology, and usually possessed an odor resembling that noted from a phenylethyl alcohol blood agar plate.